Molecular and serological investigations of Batai virus in cattle and goats in the border area of Yunnan, China (2021–2022) - Lu, Zishuo; Yan, Xingxiu; Fan, Guiying; Li, Lixia; Sun, Xiutao; Lu, Huijun; Jin, Ningyi; Liu, Hao; Sun, Wenchao (Frontiers in Veterinary Science, 2024)
Introduction Batai virus (BATV), a zoonotic pathogen transmitted by mosquitoes, infects vertebrates, including livestock, birds, and humans. Although BATV has been detected and isolated in mosquitoes in Yunnan Province, China, there have been no reports of livestock infection. Thus, we conducted a molecular and serological investigation of BATV in cattle and goat sera collected in spring and autumn from 2021 to 2022 in Honghe Prefecture, Yunnan Province, on the China-Vietnam border. Methods We used indirect enzyme-linked immunosorbent assays and reverse transcription real-time PCR (RT-qPCR) to test 929 cattle and 973 goat serum samples. Results BATV antibodies were detected in 262/929 (28.2%) cattle and 263/973 (27.0%) goat serum samples. RT-qPCR did not detect BATV RNA. Discussion The positive rate of BATV serum antibodies in cattle and goats in Luxi County was higher compared with other areas, and it was also higher in autumn compared with spring, which may be related to climate, temperature, and mosquito density. Although our findings indicated the presence of BATV infection in livestock in the region, RT-qPCR did not detect BATV RNA. Therefore, BATV monitoring in cattle and goats should be heightened in autumn, and the scope of host monitoring should be expanded to clarify the hosts and vectors of BATV infection.